THE FORMATION OF COMPETENCE IN JUNIOR PUPILS IN THE CONTEXT OF MODERN EDUCATIONAL REFORM - Khoma, Olga; Liba, Oksana (Educological discourse, 2018)
The modern approaches to the education of junior pupils in the context of educational reform have been revealed in the article. Attention has been focused on the formation of communicative and mathematical competences among junior pupils. The researches of scientists on the given problem, separate legislative acts, the content of the key word «competence» have been analyzed. The key issue in the teaching of junior pupils is the transition from accumulation of knowledge to the ability to apply it in society. The studies of ways, methods, and techniques of this process have been identified as relevant. The methods of scientific research have become: theoretical analysis of methodological literature, pedagogical observation, conversation with primary school teachers. The emphasis has been made on the formation of mathematical competence and communicative that is connected with the ability of the individual to speak the state Ukrainian language (with deep respect for the languages of the national communities) and which can become the basis for an integrated lesson. The authors have formulated a competence approach as the focus of education on the formation of complex key and subject competencies in connection with the acquired values. It has been investigated that the first important steps in the implementation of the Concept of the New Ukrainian School are: to improve the requirements for a modern lesson, its structure, methods of teaching; the definition of subject competencies within each class and subject for the possibility of integrating the topics; the formation of values through the selection of texts of different genres for language analysis (compiling them according to the teacher’s assignments), tasks, etc. Separate competency tasks in the Ukrainian language and mathematics for the implementation of the content and objectives of education at primary school have been chosen. Among them: creative tasks in the Ukrainian language, with a communicative orientation in mathematics. The role of interactive learning as an innovation in the process of competence development has been indicated. It has been investigated that younger pupils learn effectively when they are united into groups voluntarily; have motivation to study; its algorithm for the task; are in a comfortable environment (the teacher manages the learning process, but does not interfere with the reasoning of the students), analyze the work performed and each participation in particular; feel success.